Metode Super Tahfidz sebagai Strategi Peningkatan Hafalan Juz Amma pada Pendidikan Anak Usia Dini - Arifin, Zainal; Makhmudah, Siti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study was motivated by the researchers’ concern over the limited ability of kindergarten-age children to memorize Juz Amma. The objectives of this research are to describe the efforts to improve children’s Juz Amma memorization through the implementation of the Super Tahfidz method, to identify the prototype of the memorization enhancement model, and to examine the validity and practicality levels of the Super Tahfidz method as an effort to strengthen Juz Amma memorization among children at TK Al Huda Nganjuk. The research employed a research and development (R&D) design, with teachers and students as the research subjects. The results of the study indicate that the implementation of the Super Tahfidz method in improving Juz Amma memorization among kindergarten children still encounters several challenges, particularly in the understanding of teachers and students regarding its application. Nevertheless, the developed model demonstrates two main components, namely the philosophical component and the implementation component, which collectively contribute to enhancing children’s memorization ability. The results of the content validity and practicality tests show that all developed learning instruments are valid and meet the criteria of practicality, making them feasible to be applied as an effective approach to improve children’s Juz Amma memorization at TK Al Huda Nganjuk.